Inovasi Model Pembelajaran pada Program Unggulan di Madrasah Aliyah: Studi Kasus di MAS Perguruan Mu’allimat Cukir Jombang - Heru Setiawan; Insani Alkahfi; Muhammad Nur Hakim (Chalim Journal of Teaching and Learning, 2026)
This study aims to describe the innovation of learning models implemented in the flagship programs of Madrasah Aliyah Swasta Perguruan Mu’allimat Cukir Jombang. The flagship programs examined include bilingual classes, tahfidz classes, and religious classes designed to enhance the quality of the learning process and students’ learning experiences. This research employed a qualitative approach using a case study method. Data were collected through classroom observations, interviews with the principal, vice principals, teachers, and documentation of learning activities. The findings reveal that learning model innovations in the flagship programs are implemented through the development of contextual learning, additional instructional time, collaboration with external institutions, differentiated learning based on students’ abilities, and the utilization of supportive learning facilities and media. These innovations contribute to increased student engagement, strengthened academic and religious competencies, and the creation of a more effective and meaningful learning environment. This study highlights that learning model innovation in madrasah flagship programs plays a strategic role in improving the quality of students’ learning processes.